Putative Mechanism of Action of Trazodone-Related Oromandibular Dyskinesia - Alan L. Schneider (Case Reports in Psychiatry)
This is a case report of three cases of trazodone-induced buccal–lingual dyskinesias. Each case demonstrated the distinct pattern of the development of this dyskinesia after trazodone exposure for several months. All cases showed abrupt cessation of the movement disorder when the drug was discontinued. One of the three cases demonstrated a highly unusual presentation of an on/off pattern of buccal dyskinesia directly related to repetitive exposure and termination of the drug trazodone. Two of the three cases had no prior exposure to any dopamine blocking agents. One of the three had a distant exposure to a dopamine antagonist. As opposed to other antidepressants, trazodone has a mechanism of action which can account for both the development and treatment of dyskinetic movements. Its metabolite, M/chlorophenylpiperazine (M-CPP) is a 5HT2C agonist capable of causing abnormal oral-facial movements in rodent models. The presence of oromandibular dyskinetic movements can occur spontaneously with age, with trazodone being a potential predisposing factor. This article will discuss proposed mechanisms for trazodone’s action with an emphasis on case reports of dystonic movements.